The Influence of Selling Price, Product Design and Brand Image on Interest in Buying a Yamaha Motorcycle at PT. Alfa Scorpii Adam Malik - Beby Jaya Putra Zalukhu; Yuli Arnida Pohan (Digital Innovation : International Journal of Management, 2024)
This study aims to determine the effect of selling price determination, product design and brand image on motorcycle buying interest at PT. Alfa Scorpii Adam Malik. The type of research used in this study uses quantitative research. The data sources used in this study are primary and secondary data sources. The data analysis technique used in this study uses descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the results of the partial test, it is known that selling price determination has a positive and significant effect on buying interest, it is known that the t-count value is 2.235 > 1.984, then partially product design has a positive and significant effect on buying interest, it is known that the t-count value is 34.534 > 1.984. And on brand image, it has a positive and significant effect on buying interest, it is known that the t-count value is 6.446 > 1.984. Simultaneously, it is known that selling price determination, product design and brand image together have a positive and significant effect on buying interest, it is known that the f-count value is 16.890 > 2.47. In the results of the multiple linear regression test, the dominant variable that has an influence is product design at 1.052.